Analysis Adherence Of Hypertension Controlling Blood Pressure In Patients At Puskesmas Pegandon - Ferina Damayanti; Ria Septiyana; Megananda Ristya Putri (CV. AFDIFAL MAJU BERKAH, 2024)
Hypertension is persistent blood pressure where systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. Obedience comes from the rude word obey which means discipline and obedience. The purpose of this research is to determine the relationship between compliance of hypertensive patients in controlling blood pressure in patients at the Brangsong I Health Center. This type of research is quantitative research with a cross sectional approach. Measurement of the level of relationship with compliance using the chi square statistical test with α = 0.05. The relationship between medication adherence rates using the Morisky Medication Adherance Scale (MMAS-8) questionnaire. Based on the results of measuring the level of compliance from 50 respondents, there were 36 respondents (72%) had a level of compliance, 14 respondents (28%) had a level of compliance that was less compliant. The relationship between blood pressure control from 50 respondents was 14 respondents (28%) had mild blood pressure, 25 respondents (50%) had moderate blood pressure while 11 respondents (22%) had severe blood pressure. The relationship between adherence to taking medication in controlling the blood pressure of patients at the Brangsong I Health Center is the relationship between adherence to taking medication and blood pressure. There is a relationship between compliance of hypertensive patients in controlling blood pressure in patients at Brangsong I Health Center